2006
DOI: 10.1016/j.smim.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian resistance to human norovirus infections

Abstract: Noroviruses have emerged as a major cause of acute gastroenteritis in humans of all ages. Despite high infectivity of the virus and lack of long-term immunity, volunteer and authentic studies has suggested the existence of inherited protective factors. Recent studies have shown that histo-blood group antigens (HBGAs) and in particular secretor status controlled by the alpha1,2fucosyltransferase FUT2 gene determine susceptibility to norovirus infections, with nonsecretors (FUT2-/-), representing 20% of European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 97 publications
5
131
0
Order By: Relevance
“…The most reasonable explanation for our different observations is that we investigated evolutionarily conserved motifs in the capsid of a chronically infected individual with constant ABO, Lewis and secretor status, properties that affect NoV susceptibility (Le Pendu et al, 2006;Lindesmith et al, 2003;Thorven et al, 2005). In contrast, Chackravarty and coworkers investigated conserved motifs among different strains from different individuals, presumably also different ethnic groups, each with unique immunity and HBGA properties.…”
Section: Discussionmentioning
confidence: 97%
“…The most reasonable explanation for our different observations is that we investigated evolutionarily conserved motifs in the capsid of a chronically infected individual with constant ABO, Lewis and secretor status, properties that affect NoV susceptibility (Le Pendu et al, 2006;Lindesmith et al, 2003;Thorven et al, 2005). In contrast, Chackravarty and coworkers investigated conserved motifs among different strains from different individuals, presumably also different ethnic groups, each with unique immunity and HBGA properties.…”
Section: Discussionmentioning
confidence: 97%
“…The capacity of a norovirus to infect a host also depends on the secretor phenotype of the host as shown by studies on volunteers (Hutson et al, 2005;Lindesmith et al, 2003). It has been demonstrated that some strains are able to infect only secretors while others are expected to infect non-secretors only (Le Pendu et al, 2006;Tan and Jiang, 2005). In parallel, field studies on authentic outbreaks conducted in Sweden revealed that all the strains recorded infected secretors only, leading the authors to wonder if non-secretors were resistant to all noroviruses (Thorven et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the susceptibility or resistance to noroviruses depends on the presence of fucoses on the surface of epithelial cells, under the control of a polymorphic genetic system (Marionneau et al, 2001). As a result, most strains of the virus can only infect a given genetic subset of the human population (Le Pendu et al, 2006;Tan and Jiang, 2005). The presence of fucoses is also required for binding a highly pathogenic RHDV strain to rabbit epithelial cells (Ruvoën-Clouet et al, 2000) and recent observations suggest the existence of two phenotypes for rabbits: secretors, which present fucoses, and non-secretors, which do not.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, HIV binding to dendritic cells is blocked by the presence of milk oligosaccharides (21). Conversely, non-secretors are better protected to infection by norovirus (70,71).…”
Section: Applications Of Hmo Analysis Determination Of Genetic Basis mentioning
confidence: 99%